Practical guide to comparative advertising : dare to compare - Corbin, Ruth M.; Bleibaum, Rebecca N.; Jirgal, Tom; Mallen, David; Dongen, Christine A. Van (Academic Press, and imprint of Elsevier, 2019)
Practical Guide to Comparative Advertising: Dare to Compare is an authoritative, engaging handbook on comparative advertising for food and non-food consumer products. Claim substantiation is a common stakeholder interest among management, advertisers, lawyers and researchers. This handbook covers the corporate culture and strategic goals that encourage comparative advertising, laws and regulations, standards for research evidence, and examples that bring the concepts to life. Of particular value to corporate brand managers, the book includes a checklist of process steps and quality controls that allow managers to orchestrate comparative ad campaigns and manage the risk of complaints from indignant competitors.